PAPR reduction in all-optical OFDM based on time interleaving odd and even subcarriers - Hmood, Jassim K.; Harun, Sulaiman Wadi (Elsevier, 2019)
In this paper, a new all-optical approach for reducing peak-to-average power ratio (PAPR) in all-optical orthogonal frequency division multiplexing (AO-OFDM) system based on time interleaving odd and even subcarriers (TIOES) is proposed and analytically modeled. In this approach, all subcarriers are initially modulated with higher modulation format such as m-array quadrature amplitude modulation (mQAM) and encoded by return-to-zero (RZ) coder. Then, odd and even subcarriers are temporally interleaved. An analytical model for estimating the impact of the interleaved time on PAPR reduction and induced nonlinear phase noise (NPN) is developed. The effect of reducing PAPR on performance of AO-OFDM system is also numerically investigated using VPItransmissionMaker® commercial software. This system utilizes an optical coupler-based inverse fast Fourier transform/fast Fourier transform. The results reveal that minimum PAPR is occurred when interleaved time between odd and even subcarriers equal to half symbol duration where the PAPR has been reduced by 3 dB. In addition, by employing proposed technique, the signal to noise ratio (SNR) is improved by about 2.5 dB at transmission distance of 800 km as compared with 4QAM AO-OFDM without PAPR technique.